5q deletion in childhood T-acute lymphoblastic leukemia at diagnosis: a case report - Yousra Sbibih; Mohammed Bensalah; Mounia Slaoui; Abderrazak Saddari; Nabiha Trougouty; Abdelilah Berhili; Rachid Seddik (Journal of Medical Case Reports)
Abstract Background We present the case of a 6-year-old Moroccan male patient of Berber ethnic origin, diagnosed with T-cell acute lymphoblastic leukemia, who exhibited a deletion of the 5q region. Case presentation The patient initially presented with classic symptoms of T-cell acute lymphoblastic leukemia, including bone pain, hepatosplenomegaly, and lymphadenopathy. Laboratory tests revealed anemia, hyperleukocytosis, and a high percentage of lymphoid blasts in both the blood and bone marrow. Immunophenotyping results confirmed that these blasts were of T-cell origin. Cytogenetic analysis identified a deletion of the long arm of chromosome 5 in a subset of the patient’s cells. Conclusion The presence of a 5q deletion in pediatric T-cell acute lymphoblastic leukemia is an unusual finding and its prognostic significance may differ from that observed in myeloid leukemias. The implications of this cytogenetic anomaly in lymphoid malignancies remain unclear and warrant further investigation. Understanding the origins and effects of such chromosomal abnormalities in T-cell acute lymphoblastic leukemia could provide deeper insights into the disease’s pathogenesis and contribute to more tailored therapeutic strategies.